A method of determination of the minimum frequencies of oscillations of imperfect ribbed cylindrical shells on elastic foundations - Gavrylenko, G.D.; Matsner, V. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
An approach to the determination of the critical frequencies of oscillations of ribbed cylindrical shells in the elastic medium (elastic foundation) with axisymmetric irregularities of their forms is proposed. The results of studies of the effect of the parameters of axisymmetric imperfections (the number of dents, their lengths and amplitudes) on the minimum frequencies of oscillations at various coefficients characterizing the elastic foundation are presented.